FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI DONOR TERHADAP KEPUTUSAN MENURUT NILAI-NILAI AGAMA - sunasa, Armanaria; puadah, Popi; Hasanah, Siti Uswatun; Luthfi, Attabik; rasyid, hamdan (Journal of Islamic Education Studies, 2022)
Abstract The level of need for kidney organs which is quite high for patients with kidney failure is not balanced with the availability of kidney organs, giving rise to the law of demand and supply (buying and selling) of kidney organs. This greatly affects the motivation of prospective donors in making decisions to become donors which has an impact on the ethical, moral and legal aspects of religion which have the potential to be ignored. One of the reasons why people sell their organs is due to poverty. Motivationto become a donor is voluntary based on knowledge, attitudes and behavior. Based on the data sources and relevant research above, this research is intended to determine the extent of the influence of donor motivation and provide motivation and attitudes for prospective kidney donors (living donors) in making decisions in accordance with religious sharia. This research uses descriptive qualitative method by digging information to people who have done donor activities. The purpose of this study is to find out what factors encourage people to donate blood and how Islam views the values contained in it